A Therapeutic Evaluation of Anticancer and Pharmacological Abilities on Tinospora cordifolia: A Systematic Review - Kumar, M. Vijaya; Reddy, H. Rama Subba; Swamy, A. Narayana; Jayappa, K.; Reddy, M. Sreekanth; Kumar, D. Veera Nagenddra; Kiran, V. Uday (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Tinospora cordifolia (Tc), commonly called as Giloy, it is a herbaceous vine that is widely used in traditional medicine systems for its alleged anti-cancer effects. The purpose of this systematic study is to assess Tinospora cordifolia’s (Tc) medicinal potential against cancer. A thorough search of various scientific databases was done for studies looking at Tinospora cordifolia's anti-cancer properties. The findings demonstrate a varied variety of In vitro and In vivo research demonstrating Tinospora cordifolia’s (Tc) anti-proliferative, apoptotic and anti-metastatic activities against many cancer types, including breast, prostate, colon, and leukaemia. Mechanistic insights into its mode of action, such as modulation of signaling pathways involved in cell cycle regulation, apoptosis and angiogenesis, are presented. However, limitations in study designs, inconsistency in methodology, and differences in reported outcomes highlight the need for more well-designed clinical trials to evaluate Tinospora cordifolia's efficacy and safety as a potential supplementary medicine in cancer treatment regimens. Therapeutic plants, such as T. cordifolia, can strengthen the body's defences against disease and cure specific areas, displaying more body compatibility and fewer side effects than medications. In conjunction with this, the current study highlights T. cordifolia's pharmacological potential against a variety of illnesses.